Choriocarcinoma following term pregnancy with successfulsubsequent pregnancy (Indian Journal of Case Reports, 2026)
Gestational trophoblastic neoplasia (GTN) denotes subtypes of gestational trophoblastic disease that have invasion potential, for example, invasive mole. Gestational choriocarcinoma (CC). Gestational CC is an extremely malignant tumor and considered the most common histologic type of GTN encountered following normal pregnancy; however,CC is a potentially curable disease, and the outlook is excellent in most cases. This case report involves clinical management and long-term follow-up of a 32-year-old female who presented 28 days after cesarean delivery with recurrent episodes of massive delayed postpartum hemorrhage. Her evaluation revealed an elevated beta-human chorionic gonadotropin level (36053.9 mIU/mL) and uterine vascular mass on pelvic ultrasound. Diagnosis of CC was confirmed histologically on the specimen retrieved during suction and curettage. The patient received 6 cycles of chemotherapy (vincristine-cisplatin) with a good response. She got pregnant 1 month after the last dose of chemotherapy. Her subsequent pregnancy was uneventful, and she gave birth to a healthy baby at 38 weeks. Such cases display a diagnostic challenge in low-resource settings and concerns regarding fertility preservation in survivors of CC.